Nutritional status and nutritional therapy in pediatric and adolescent patients submitted to autologous hematopoietic stem cell transplantation - Härter, Jéssica; Gregianin, Lauro José; da Cruz, Luciane Beitler (Clinical and Biomedical Research, 2021)
Introduction: To assess the use of nutritional support in children and adolescents submitted to autologous hematopoietic stem cell transplantation (HSCT), and analyze changes in nutritional status at hospital discharge after HSCT. Methods: A retrospective observational study was conducted on pediatric oncology patients hospitalized for autologous HSCT between 2010 and 2017. Nutritional therapy was evaluated based on the duration of enteral tube feeding (ETF) and parenteral nutrition (PN), either alone or in combination. The length of hospital stay was measured in days. Nutritional status was assessed at admission and discharge, and classified according to World Health Organization criteria. Results: The sample consisted of 68 patients, 54.4% of whom were boys. Most participants (89.7%) had solid tumors. Nutritional therapy was required in over half (52.9%) of cases, with PN being the most common indication. There was a reduction in the percentage of overweight patients and an increase in the percentage of underweight patients at discharge relative to admission. Conclusions: The use of nutritional therapy is highly prevalent in this population, and HSCT has a negative impact on nutritional status at discharge.